Potentially inappropriate medication use in the elderly: physicians’ and hospital pharmacists knowledge, practice, confdence, and barriers (2020)
Background: Inappropriate medication prescribing and dispensing by physicians and pharmacists is a preventable cause of morbidity and mortality in the elderly. Signifying the importance of healthcare professionals’ knowledge of potentially inappropriate prescribing tools/ guidelines which would improve overall health outcomes. Beers Criteria is one of the most used guidelines that list specifc potentially inappropriate medications (PIMs). This study aimed to investigate physicians’ and hospital pharmacists’ awareness, knowledge, practice, confdence, and barriers to the use of Beers criteria. Methods: A cross-sectional survey was carried out among 66 hospital pharmacists and 31 family medicine physi cians working in a teaching hospital in Nigeria, between May and September 2021 using a self-administered ques tionnaire. Knowledge of PIMs was assessed using 11 clinical vignettes based on the 2019 Beers Criteria. Practice behavior towards elderly patients was assessed using a 5-item statement with a 5-point Likert scale. Perceived barriers to the appropriate use of Beers Criteria were assessed using a 15-item statement. Descriptive and inferential statistics were used to analyze the data. Results: A total of 66 hospital pharmacists and 31 family medicine physicians participated in the study. Only (24; 36.4%) pharmacists and (4; 12.9%) physicians knew guidelines that listed specifc PIMs. In all (21; 31.8%) pharmacists and (11; 35.4%) physicians demonstrated good knowledge of Beers Criteria, while most pharmacists (55; 83.3%) and physicians (29; 93.5%) reported good practice when dealing with elderly patients in terms of asking relevant ques tions and considering their ages while dispensing medications. Knowledge scores were not signifcantly associated with hospital pharmacists’ socio-demographics. Most of the physicians and pharmacists were confdent in the care provided for geriatric patients. The majority (66; 100.0%) pharmacists and (28; 93.5%) physicians suggested training through seminar presentations as a measure to improve the use of Beers’ criteria. Lack of time to counsel patients was a major barrier recounted by both physicians and pharmacists. Conclusion: Healthcare professionals that participated in this study had satisfactory practice, although a gap in the knowledge of hospital pharmacists and family medicine physicians was noted. In addition to creating aware ness among healthcare professionals and training on PIMs and Beers’ criteria, a multidisciplinary approach to reduce potentially inappropriate prescribing and dispensing would greatly help reduce the incidence of potentially inappro priate medication use among elderly patients.